CTA Annual Report 2015 - A year in review: Advancing agricultural transformation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2016)
With 2015 came the start of a new strategic plan for CTA, entitled Sowing Innovation, Harvesting Prosperity. The plan, which is discussed in this review, will guide the Centre’s valuable work up until 2020 towards a greater emphasis on agribusiness development, climate-smart agriculture and nutrition-sensitive agri-food systems. The year also saw CTA securing new sources of funding, working to scale up ICTs to benefit large numbers of farmers and its involvement in many successful events. These included the Caribbean-Pacific Agri-Food Forum, which focused on promoting the engagement of the private sector and farmers’ organisations in transforming agriculture in the region, and numerous meetings on ‘open data’.